Changes in Greenhouse Grown Tomatoes Metabolite Content Depending on Supplemental Light Quality - Alsina, Ina; Erdberga, Ieva; Duma, Mara; Alksnis, Reinis; Dubova, Laila (Frontiers in Nutrition, 2022)
Tomatoes (Solanum lycopersicum L.) is good source of several biologically active compounds and antioxidants, especially lycopene, phenolic compounds and vitamins. Tomatoes are found all over the world and are cultivated in a wide variety of environmental conditions. LED lamps are increasingly being used in the cultivation of tomatoes due to their cost-effectiveness and wide range of possibilities to adapt the spectrum of light emitted to the needs of plants. The aim of this study is to evaluate the effect of different additional lighting used in the greenhouse on the accumulation of biologically active compounds in different varieties of tomato fruit. Chemical composition - content of organic acids, lycopene, total carotenoids, total phenolics and flavonoids as well as dry matter, content of soluble solids and taste index were determined in five tomato cultivars ('Bolzano F1', 'Chocomate F1', ‘Diamont F1’, 'Encore F1', 'Strabena F1'), which were cultivated in greenhouse in autumn-spring season using additional lighting with 16 h photoperiod. Three different lighting sources were used: LED, induction lamp (IND) and high pressure sodium lamp (HPSL). Experiments were performed during 3 years. Results showed that tomato varieties react differently to the supplemental lighting used. Cultivars ‘Encore’ and ‘Strabena’ are the most unresponsive to supplemental light. Experiments have shown that HPSL stimulates the accumulation of primary metabolites in tomato fruit. In all cases, a soluble solids content was 4.7 - 18.2 % higher compared to other lighting sources. As LED and IND lamps emit about 20% blue-violet light, the results suggest that blue-violet light of the spectrum stimulates the accumulation of phenolic compounds in the fruit by 1.6% - 47.4% under IND, and 10.2-15.6% under LED compared to HPSL. Red fruit varieties tend to synthesize more β-carotene under supplemental LED and IND light.